A simple spectrophotometric method for the determination of captopril in pharmaceutical preparations using ammonium molybdate - Ribeiro, P. R. S; Pezza, Leonardo [UNESP]; Pezza, Helena Redigolo [UNESP] (Editora Unesp, 2010)
Um método simples, rápido e sensível para a determinação espectrofotométrica de captopril (CPT) em formulações farmacêuticas é proposto. Este método é baseado na reação de redução do molibdato de amônio, na presença de ácido sulfúrico, pelo grupo tiol do CPT, produzindo um composto verde (λ max 407 nm). A lei de Beer é obedecida na faixa de concentração de 4,60 x 10-4 a 1,84 x 10-3 mol L-1 de CPT com um excelente coeficiente de correlação (r = 0,9995). O limite de detecção e o limite de quantificação foram de 7,31 x 10-6 e 2,43 x 10-5 mol L-1 de CPT, respectivamente. O método proposto foi aplicado com sucesso na determinação da CPT em amostras comerciais de produtos farmacêuticos. Não foram observadas interferências dos excipientes comumente encontrados nas formulações farmacêuticas. Os resultados obtidos pelo método proposto foram comparados favoravelmente com aqueles obtidos pelo método oficial relatado em um nível de 95% de confiança.

A simple, rapid and sensitive spectrophotometric method for the determination of captopril (CPT) in pharmaceutical formulations is proposed. This method is based on the reduction reaction of ammonium molybdate, in the presence of sulphuric acid, for the group thiol of CPT, producing a green compound (λ max 407 nm). Beer's law is obeyed in a concentration range of 4.60 x 10-4 - 1.84 x 10-3 mol l-1 of CPT with an excellent correlation coefficient (r = 0.9995). The limit of detection and limit of quantification were 7.31 x 10-6 e 2.43 x 10-5 mol l-1 of CPT, respectively. The proposed method was successfully applied to the determination of CPT in commercial brands of pharmaceuticals. No interferences were observed from the common excipients in the formulations. The results obtained by the proposed method were favorably compared with those given by the official reported method at 95 % confidence level.
Keywords: Captopril; determinação espectrofotométrica; molibdato de amônio; Captopril; spectrophotometric determination; ammonium molybdate